What is a document institution? A case study from the South Sami community - Grenersen, Geir (Journal of Documentation, 2012)
The Sámis are the indigenous population of Northern Scandinavia. When the oppressive policy against the Sámi population in Norway was lightened during the 1960s, many Sámi communities established language and cultural centers for documentation and development of their language and cultural heritage as the oral tradition lost its ground in the modernization process. This paper aims to discuss how Sámi cultural centers use documentation both as a way of remembering the past and as a political strategy in order to produce evidence for land and water claims. The Sámi centers are many-faceted institutions and document theory is suggested as a theoretical perspective in order to analyze why these institutions were established and how they are functioning today. Two cases are presented. The first shows how the centers use documentation as a technique for restoring the past. The second is a ruling in the Norwegian High Court that shows a new turn in what can be accepted as documents proving indigenous land and water claims. This article is an attempt to introduce document theory as an analytical tool for analyzing the documentation processes in indigenous cultural centers.